Study the Inhibition of some Toxicants on the Luminescent Ability of Vibrio fischeri - Tran Thi Huyen, Nga (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1S, 2017)
This research focused on the relationship between concentrations of some toxic chemicals in the water and their influence on the luminescence of Vibrio fischeri (heavy metals: Pb (II), Hg (II), As (V), pesticides: DDT, Lindane and 2,4D). Experiments carried out with the following concentrations: Pb (II) 0,003-0,75 mg/L; As(V) 0,8-102,4 mg/L; Hg(II) 0,0012-0,16mg/L; DDT 40-70mg/L; 2,4 D 15-45 mg/L; Lindane 35-55 mg/L, the luminescence was investigated after 5, 10, 15, 30, 45 minutes. EC value (the effect concentrations of toxicant) represented the threshold of organism by toxicant, the lower the EC (50) , the less the concentration of a toxicant is required to harm (reduce the luminescence). The results figured that the toxicants (three heavy metals Pb, As, Hg and three organic chemicals DDT, 2,4D, Lindane) can reduce the luminescence of Vibrio fischeri at low concentration. The EC 50 of six toxicants were Pb (II): 0,02 ± 0,01 mg/L; As (V): 2 ± 0,2 mg/L; Hg (II): 0,04 ± 0,01 mg/L; DDT: 50 ± 1 mg/L; 2,4 D: 27±1 mg/L; Lindane: 42±1 mg/L.